Intelligent Systems in Cybernetics and Automation Control Theory - Silhavy, Radek; Silhavy, Petr; Prokopova, Zdenka (Advances in Intelligent Systems and Computing,, 2019)
This book presents real-world problems and pioneering research that reflect novel approaches to cybernetics, algorithms and software engineering in the context of intelligent systems. It gathers the peer-reviewed proceedings of the 2nd Computational Methods in Systems and Software 2018 (CoMeSySo 2018), a conference that broke down traditional barriers by being held online. The goal of the event was to provide an international forum for discussing the latest high-quality research results. .